2011
DOI: 10.1111/j.1365-3024.2011.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Triggering receptor expressed on myeloid cells (TREM)‐1 participates in Schistosoma mansoni inflammatory responses

Abstract: Inflammatory responses to microbial products are amplified by a pathway mediated by triggering a receptor expressed on the myeloid cells (TREM)-1. Relatively a few studies have been performed to investigate the role of TREM-1 in macrophage activation in response to parasitic infection. In this study, we delineate the role of the innate immunoreceptor TREM-1 in the parasite Schistosoma mansoni infection model from early to late (chronic) phases of infection. Flow cytometry analysis revealed gradual increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…TREM-1 is a DAP12-associated receptor expressed on neutrophils and monocytes ( 57 ) that plays a key role in the protecting the host against fungal allergens ( 58 ), parasites ( 59 ) as well as in bacterial sepsis ( 60 , 61 ), collagen-induced arthritis ( 62 ), and inflammation-associated tumor development ( 63 ). Interesting studies have also suggested that TREM-1 is involved in neutrophil migration across the epithelium ( 64 ) and macrophage infiltration at pathological sites ( 63 ) thus providing a possible explanation for the amplified inflammatory response we observed in our system.…”
Section: Discussionmentioning
confidence: 99%
“…TREM-1 is a DAP12-associated receptor expressed on neutrophils and monocytes ( 57 ) that plays a key role in the protecting the host against fungal allergens ( 58 ), parasites ( 59 ) as well as in bacterial sepsis ( 60 , 61 ), collagen-induced arthritis ( 62 ), and inflammation-associated tumor development ( 63 ). Interesting studies have also suggested that TREM-1 is involved in neutrophil migration across the epithelium ( 64 ) and macrophage infiltration at pathological sites ( 63 ) thus providing a possible explanation for the amplified inflammatory response we observed in our system.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding Schistosoma infection, some substances from Schistosoma eggs may inhibit the expression of TREM-1 on mouse macrophages. This mechanism can decrease the macrophage-mediated inflammatory response in infected hosts [28]. On the other hand, neutrophils infected by L. infantum enhance the transcription of TREM-1 and molecules associated with its activation as well as the release of sTREM-1.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have explored the role of TREM-1 in inducing inflammation in multiple contexts, such as sepsis [9,21], cancer [22], viral infections [23,24], and others non-infectious diseases [25,26]. However, the role of TREM-1 signaling in innate immunity against parasite infections and its underlying mechanisms remain unknown [13,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The method was modified as our previously reports described [ 35 ]. The spleens of sacrificed mice were removed and placed in a Petri dish and then washed to flush out the spleen immune cells.…”
Section: Methodsmentioning
confidence: 99%